Haemolytic anaemia precipitated by dengue fever. Issue 8 (28th August 2019) - Abdullah, Nurul Huda; Mohammad, Nurashikin; Ramli, Marini; Wan Ghazali, Wan Syamimee
Abstract : We reported a case of a woman with no past medical illness who presented with a few days' history of fever, myalgia, arthralgia, hypochromic microcytic anaemia and thrombocytopaenia and who was nonstructural protein 1 antigen (NS1Ag)-positive. Haemolytic anaemia including full blood picture work-up revealed high reticulocyte count and haemolysis with positive direct Coombs test. She was started on prednisolone and was discharged well.